Enhanced water adsorption properties of Ti3C2Tx MXene/bentonite thin films for highly sensitive humidity sensing - Hiroya Morotomi; Yuki Matsunaga; Lijun Liu; Hisashi Sugime; Jun Hirotani (AIP Advances)
Humidity sensors are integral to modern technology and extensively utilize Ti3C2Tx MXene for its superior sensitivity and accuracy. This material’s effectiveness stems from its abundant hydrophilic functional groups and high electrical conductivity. In this study, we enhanced the responsiveness to relative humidity changes by incorporating bentonite, a 2D clay mineral known for its robust water adsorption capacity and ionic conductivity, attributable to its distinctive structure. Our analysis of MXene/bentonite thin films through sheet resistance measurements indicated a clear inverse relationship in resistance changes above and below a specific MXene-to-bentonite ratio. Impedance analysis further revealed that the dominant conduction mechanisms within these films vary according to the mix ratio. In fabricating conductive-type humidity sensors from MXene/bentonite films, we observed a remarkable increase in humidity sensitivity. Particularly, MXene rich film (33 wt. % MXene) demonstrated a sensitivity of ∼58.1 times greater than MXene film, and bentonite rich film (10 wt. % MXene) demonstrated about 5000 times greater than MXene film. This study not only underscores the potential of MXene/bentonite composites in humidity sensing but also highlights the critical role of composition in optimizing sensor performance.